Dynamics of Economic Growth of the Global Halal Industry: A Systematic Literature Review of Business Innovation Models and Its Implications for the Economic Development of the Humanity - Khilma Mumtazah (Majapahit Journal of Islamic Finance and Management, 2026)
This research analyzes the dynamics of global halal industry economic growth through a systematic literature review of business model innovation and its implications for Ummah economic development. Implementing Systematic Literature Review methodology with PRISMA protocol, the study identifies ten primary articles from 2015 to 2025 sourced from Scopus and Web of Science databases. Findings reveal three fundamental dimensions: first, halal industry business model innovation evolution driven by digital technology 4.0 integration creating value ecosystems based on blockchain, Internet of Things, and e-commerce with USD 6.49 trillion market projection by 2034; second, implementation success disparities across Muslim countries determined by digital infrastructure maturity, certification regulation harmonization, and multi-stakeholder strategic collaboration; third, digital technology and global standardization convergence accelerates economic development through consumption expansion, employment creation, and foreign investment enhancement. The research contributes to developing an integrative conceptual framework connecting business innovation, digital transformation, and sustainable economic development within the halal industry context, providing a strategic roadmap for policymakers and industry practitioners.